(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2018)
Introduction: GeneXpert MTB/Rif assay is an automated, cartridge-based nucleic acid amplification test that can accurately detect both tuberculosis and Rifampicin resistance. Since its introduction, there has been a steady uptake of this technology by the National Tuberculosis Program of Nepal. Nevertheless, a large number of drug-resistant TB cases remains undiagnosed. This study aims to examine the challenges in diagnosis of drug-resistant tuberculosis by the GeneXpert MTB/Rif assay in Nepal and explore the possible solutions. Methods: This was a cross-sectional study consisting of two parts – a quantitative part assessing the individual details and a qualitative part assessing the challenges on the diagnosis of drug-resistant TB by GeneXpert MTB/Rif assay. Data were collected from the GeneXpert operators, clinicians and program managers from 16 centers across the country and analyzed by IBM SPSS for Windows v23 and QDA Miner 4 Lite. Descriptive statistics were used to summarize the sociodemographic and other characteristics of the study participants using mean, standard deviation and proportions as appropriate. Results: A total of 48 technical manpower participated in the study. The mean age was 39.95 years and a majority of them (77.3%) were male. The major challenges identified were inadequate training, frequent power failure, difficulty in maintaining appropriate steady temperature, module failure which is often not replaced in time, issues with calibration and timely availability of cartridges as well as appropriate ways to store the new cartridges and safe disposal of the used cartridges. Conclusion: A number of challenges limit the optimal utilization of GeneXpert MTB/Rif assay warranting action.